2014
DOI: 10.1007/s11356-014-3628-7
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to neonicotinoid insecticides for pest control: case studies in agriculture and forestry

Abstract: Neonicotinoid insecticides are widely used for control of insect pests around the world and are especially pervasive in agricultural pest management. There is a growing body of evidence indicating that the broad-scale and prophylactic uses of neonicotinoids pose serious risks of harm to beneficial organisms and their ecological function. This provides the impetus for exploring alternatives to neonicotinoid insecticides for controlling insect pests. We draw from examples of alternative pest control options in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 84 publications
1
71
0
Order By: Relevance
“…That said, our finding is consistent with previous meta-analyses (Naranjo, 2009; Wolfenbarger et al, 2008) that found a negative effect of pyrethroids on predatory arthropods (versus transgenic Bt varieties) of similar magnitude to the negative effect we found for seed-applied neonicotinoids (versus untreated controls). Pyrethroids are the second most widely used class of insecticides in the world after neonicotinoids (Sparks, 2013), and are important alternatives to seed-applied neonicotinoids in North American and European field crops (Budge et al, 2015; Douglas & Tooker, 2015; Furlan & Kreutzweiser, 2015). Their use is therefore likely to increase if, when, and where neonicotinoid use is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…That said, our finding is consistent with previous meta-analyses (Naranjo, 2009; Wolfenbarger et al, 2008) that found a negative effect of pyrethroids on predatory arthropods (versus transgenic Bt varieties) of similar magnitude to the negative effect we found for seed-applied neonicotinoids (versus untreated controls). Pyrethroids are the second most widely used class of insecticides in the world after neonicotinoids (Sparks, 2013), and are important alternatives to seed-applied neonicotinoids in North American and European field crops (Budge et al, 2015; Douglas & Tooker, 2015; Furlan & Kreutzweiser, 2015). Their use is therefore likely to increase if, when, and where neonicotinoid use is restricted.…”
Section: Discussionmentioning
confidence: 99%
“…A range of concerns have emerged as to the impacts of neonicotinoids and fipronil on the environment Pisa et al 2014;Gibbons et al 2014;Chagnon et al 2014;Furlan and Kreutzweiser 2014):…”
Section: The International Scientific Task Force On Systemic Pesticidmentioning
confidence: 99%
“…Impacts on such a broad range of organisms ultimately also affect ecosystem functioning (17). As a result, the pertinence of use of these pesticides is currently being questioned in many countries (18), with a ban now implemented in France, and alternatives proposed (19). However, despite increasing research efforts to understand the patterns of neonicotinoid uses and their effects on living organisms, we lack a global view of the worldwide distribution of neonicotinoid contamination in the environment (18) to evaluate the risk posed to living organisms.…”
mentioning
confidence: 99%